Microchilus culuenensis (Orchidaceae, Goodyerinae): a new species from Southearn Brazilian Amazon - Engels, Mathias E.; Smidt, Eric C. (Phytotaxa, 2024)
During the UFMT Herbarium collection study, an undescribed species of Goodyerinae (Orchidaceae) was found on the banks of the Culuene River, a tributary of the Alto Xingu basin, state of Mato Grosso, Southern Brazilian Amazon. We described and illustrated Microchilus culuenensis, a species morphologically related to M. amazonicus, M. juruenensis and M. stigmatopterus, which can be differentiated from them by a set of characteristics: narrow-lanceolate leaves, lip with an oblong callus and truncated at the mesochile, presence of a rounded, bilobed callus in the center of the epichile, and a rounded apex of the lobes of epichile. The new species is classified as Data Deficient (DD) regarding the conservation status.